Video-based learning for Higher Education 4.0 in Malaysia, Indonesia and Brunei / Airil Haimi Mohd Adnan - Mohd Adnan, Airil Haimi (2021)
Higher Education 4.0 is a worldwide initiative in the tertiary teaching and learning industry that ensures the knowledge being shared by tertiary instructors are similar to the future working experiences of their students. Many sweeping changes are occurring due to Industry 4.0. One way that the nature of 'working' is being changed is in how training is being done at this moment in time. Tertiary learners as future employees are progressively being exposed to learning technologies and tools that are endemic to Higher Education 4.0, one of them is the concept of video learning or video-based learning (VBL). VBL is a primary catalyst of the 'flipped classroom' initiative and it aids in the delivery of blended lessons, predominantly at universities and tertiary colleges. In the ASEAN region, VBL is empowering not just learners but also tertiary instructors who can now ensure that access to learning will be open 24/7, and that learners will be able to access knowledge whenever and wherever they want. Short, amusing, engaging, and illuminating videos are the future of learning through the Higher Education 4.0 movement. This empirical study is based on previous concerted initiatives to create and share 'explainer video clips' to teach in a wider, more open and accessible manner focusing on key points and highlights that tertiary learners need to expand on their own. At present, VBL is not just a form of informal learning, it is becoming a common tool across the academic and corporate learning divide